Philosophical origins of psychology (Journal Of Educational and Psychological Researches, 2017)
Since the beginning of Philosophical thinking, philosophers had interested in matters that related to psychology. Greek philosophy had sought different psychological cases such as knowledge, thought, sense, and cognition. Plato classified cognitive processes and distinguished between intelligence, emotions, and desires. As Aristotle believed that soul is the essence of human beings that characterize it from other creatures. Regarding the European philosophy, Descartes linked the optics field to psychology that comprises theories about visual perception. Then, john Watson who interested in behaviorism, he believes that the interpretation of behavior will be materialistic. However, the evolutionary view had great effect on psychology that could be observed in Freud theory “desire system.” formative Simeologia of Piaget relied on child psychology to know how to develop concepts. Marxist Psychology believed that the existence of human is fundamental.